Effect of pre-exposure use of hydroxychloroquine on COVID-19 mortality: a population-based cohort study in patients with rheumatoid arthritis or systemic lupus erythematosus using the OpenSAFELY platform - Rentsch, CT; DeVito, NJ; Bacon, S; MacKenna, B; Morton, CE; Bhaskaran, K; Brown, JP; Schultze, A; Hulme, WJ; Croker, R; Walker, AJ; Williamson, EJ; et al. (Elsevier, 2020)
Background Hydroxychloroquine has been shown to inhibit entry of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) into epithelial cells in vitro, but clinical studies found no evidence of reduced mortality when treating patients with COVID-19. We aimed to evaluate the effectiveness of hydroxychloroquine for prevention of COVID-19 mortality, as opposed to treatment for the disease.